PENGEMBANGAN PENDIDIKAN ISLAM BERKUALITAS DI INDONESIA - Adi Purwanto (DIA: Jurnal Administrasi Publik, 2019)
The purpose of this study is to formulate the efforts that can be done to develop the quality of Islamic Education in Indonesia. The type of research is descriptive qualitative. The data used in this study are qualitative data that are collected using literature study method and processed using qualitative analysis techniques. The study findings suggest that efforts to develop the quality of Islamic Education in Indonesia include: 1) Integrating products from the development and advancement of science and technology into the Islamic Education system; 2) Applying a comprehensive approach and learning method that combines Islamic education provided at school, in the family, and in society, balanced by communicative delivery and exemplary practice of Islamic values; 3) Implementation of quality management of Islamic Education covering the management of educational institutions and all components of education in it, including teachers, learners, educational facilities, learning process, and community relations; 4) Increasing the welfare of teachers to encourage the improvement of the work ethos, which in turn will be able to contribute maximally in improving the quality of Islamic Education; and 5) Directing learning practices in Islamic Education on the purpose of increasing understanding, mastery, and application of Islamic values by learners.